Statistical Analysis in Determining the UIN Kiai Haji Achmad Siddiq (UIN KHAS) Jember Students' Readiness Toward the Internet-Based Learning System - Azwar Habibi (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2022)
This research focuses on finding out how far the readiness of UIN KHAS Jember students in facing this e-learning learning system is, so research is carried out in the form of a survey. From the survey results, it is hoped that data can be obtained regarding what factors influence the e-Learning-based learning system to be applied to UIN KHAS Jember students. The variables used are Study Habits and Technology Habits. The data analysis method used in this research is the 1 sample proportion test and the Chi-Square test. Respondents used were UIN KHAS Jember students Class of 2015, 2016, 2017, and 2018. From a series of data collection to the analysis stage, several conclusions can be drawn, namely the number of UIN KHAS Jember students ready to face the e-learning learning system by 60% (or more than 50% of students). The variables that affect student readiness in dealing with e-learning learning systems are study habits and technology habits. From each of these variables, it turns out that only the attitude factor towards the learning system and the length of time on the internet are very significant or affect student readiness.